THE PERCEPTION ABOUT DIFFICULTIES OF DIALECT BUGINESE TOWARD STUDENT’S SPEAKING IN MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Rina Indrianty Ridwan; Ahmad Munir; Oikurema Purwati (Universitas Muhammadiyah Makassar, 2022)
The difficulty of speaking English, especially for first graders It will be a sustainable issue. Seeing that phenomenon, this study aimed to see difficulty in speaking English among first graders of English education Muhammadiyah University of Makassar. There are two in this study. This study takes a qualitative approach of choosing a location and choosing Students will batch 2020 as a participant in this study. Participants were selected through recommendations from all instructors who taught the course. About difficulty in speaking English, 4 difficulties in this study. The result was Interference from students' dialect according to the research results, the dominant the interference to students‟ spoken language is interfere with pronunciation stress any part of the word. Student dialect factors difficulties speaking English (internal factor = self-confidence) main distractions to students performance was an interference with spoken language performance lasses that make students more confident, those students who felt wrong in the lecture English and their friends can’t understand because they spoke English was like they speak the local dialect, it interferes the motivation of the student to speak.